Carta de Manuel F. Rossy a Roberto H. Todd - Todd, Roberto H.; Rossy, Manuel F. (My University, 1921)
Reflexiones sobre la ambivalencia ideológica de los unionistas.
Keywords: Partido Republicano (Puerto Rico); Republican party. Puerto Rico.; Córdova Dávila, Félix, 1878-1938